2006
DOI: 10.1063/1.2404671
|View full text |Cite
|
Sign up to set email alerts
|

Infrared photodissociation spectroscopy of protonated ammonia cluster ions, NH4+(NH3)n (n=5–8), by using infrared free electron laser

Abstract: Infrared photodissociation action spectra of protonated ammonia cluster ions, NH(4) (+)(NH(3))(n) (n=5-8), were measured in the range of 1020-1210 cm(-1) by using a tunable infrared free electron laser. Analyses by the density functional theory (DFT) show that the spectral features observed can be assigned to the nu(2) vibrational mode of the NH(3) molecules in NH(4) (+)(NH(3))(n). Size dependence of the spectra supports structural models obtained by the DFT calculations, in which the NH(4) (+) ion is solvated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
28
2
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 20 publications
5
28
2
2
Order By: Relevance
“…[14] For larger systems (n = 3-9), photodissociation spectra at longer wavelengths have been reported using a line-tunable CO 2 laser [15] or a free electron laser. [16,17] These studies have shown that while the n > 1 clusters prefer to form an ammonium ion solvated by ammonia molecules, the protonated ammonia dimer is unique in that it adopts a D 3d equilibrium geometry, with the excess proton shared equally between two ammonia molecules. Computationally, the structure and spectroscopic characteristics of (NH 4 + )(NH 3 ) n clusters have been studied mainly within the harmonic approximation (see references [18,19] and references therein) or using an effective onedimensional quantum model [20] of the N···H + ···N sharedproton stretching vibration in N 2 H 7 + .…”
mentioning
confidence: 99%
“…[14] For larger systems (n = 3-9), photodissociation spectra at longer wavelengths have been reported using a line-tunable CO 2 laser [15] or a free electron laser. [16,17] These studies have shown that while the n > 1 clusters prefer to form an ammonium ion solvated by ammonia molecules, the protonated ammonia dimer is unique in that it adopts a D 3d equilibrium geometry, with the excess proton shared equally between two ammonia molecules. Computationally, the structure and spectroscopic characteristics of (NH 4 + )(NH 3 ) n clusters have been studied mainly within the harmonic approximation (see references [18,19] and references therein) or using an effective onedimensional quantum model [20] of the N···H + ···N sharedproton stretching vibration in N 2 H 7 + .…”
mentioning
confidence: 99%
“…Gas‐phase IR spectroscopy of N 2 H 7 + , the Zundel cation analogue in protonated ammonia clusters (NH 4 + )(NH 3 ) n , has to date been restricted to the range above 2600 cm −1 14. For larger systems ( n =3–9), photodissociation spectra at longer wavelengths have been reported using a line‐tunable CO 2 laser15 or a free electron laser 16. 17 These studies have shown that while the n >1 clusters prefer to form an ammonium ion solvated by ammonia molecules, the protonated ammonia dimer is unique in that it adopts a D 3 d equilibrium geometry, with the excess proton shared equally between two ammonia molecules.…”
Section: Experimental and Calculated Vibrational Frequencies (In Cm−1mentioning
confidence: 99%
“…This study in particular suggested that in the smallest cluster, N 2 H þ 7 , the proton is equally shared between the two ammonia molecules, i.e., midway between the two N atoms. Subsequent investigations of clusters ranging from n ¼ 3 to 8 payed special attention to the spectral signatures of the solvation shell structure [13][14][15]. Very recently the gas phase IR spectrum of N 2 H þ 7 in the region below 1000 cm À1 has been reported [16,17] and the frequency of the fundamental asymmetric stretching vibration of the shared proton was found to be as small as 374 cm À1 .…”
Section: Introductionmentioning
confidence: 97%